False cognates and english communicative skills in the students of the Language Center of the Private University of Tacna, 2022 - Garcia Ponce, Lorena Sahori (2023)
The objective of the research was to establish how the learning of false cognates is related to the mastery of communicative skills of the English language in the students of the Language Center of the Private University of Tacna, 2022. The methodology of the present research was basic, of correlational level with non-experimental sectional design. The sample population was 221 from the language center of the Private University of Tacna, enrolled in the 2022-II academic year. The applied instruments were subjected to validity by expert judgment using Aiken's V and reliability through Cronbach's Alpha, obtaining adequate results (.899 and .908 respectively). The results indicate that 36.2% of the students reached the regular level in the variable learning false cognates. Regarding the variable Mastery of English language communication skills, it was revealed that 42.1% present a good level. It is concluded that the learning of false cognates is directly, positively related to the mastery of communicative skills of the English language in the students of the Language Center of the Private University of Tacna, 2022 (rs= 0.729; p= 0.000).